CAUSAL ATTRIBUTIONS OF UNIVERSITY STUDENTS - Şenay YAPICI (Fırat University, 2019)
The purpose of the research is to find out the dimensions of the causal attributions to success and failure of university students. The study group consisted of 1. and 4. grade students of three faculties of Education, Engineering and Economics and Administrative Sciences in the academic year of 2010-2011. The sample consisted of a sum of 300 people, 136 of whom are male, and 164 of whom female. Causal Dimensions Scale II adapted from McAuley, Duncan, and Russell (1992) was used as the data collecting tool. As a result of the research, attributions to success were found out to be more internal, personally more controllable, stable, but externally less controllable. Attributions to failure are more external, externally more controllable but personally less controllable and stable than the ones to success.